2013
DOI: 10.7845/kjm.2013.3048
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics with Antimicrobial Activity against Multidrug Resistant Pseudomonas aeruginosa and Acinetobacter baumannii

Abstract: Pseudomonas aeruginosa and Acinetobacter baumannii are significant opportunistic pathogens in hospitals and are resistant to most antibiotics. Multidrug-resistant P. aeruginosa (MDRPA) and A. baumannii (MDRAB) cause severe human nosocomial infections and are more difficult to treat than methicillin-resistant Staphylococcus aureus (MRSA). Bifidobacteria are among of the most beneficial probiotics and have been widely studied for their antimicrobial activities. The present study explored the antimicrobial activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Jamalifar et al ( 154 ) reported strong antagonistic activity of Lactobacillus acidophilus fecal isolate against the MDR clinical isolate of Pseudomonas aeruginosa . On similar lines, Bifidobacterium pseudocatenulatum SPM1309 was shown to inhibit MDR P. aeruginosa and A. baumannii ( 155 ). Lactobacillus casei strain exhibited strong activities against MDR Shigella strain ( 156 ).…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 88%
“…Jamalifar et al ( 154 ) reported strong antagonistic activity of Lactobacillus acidophilus fecal isolate against the MDR clinical isolate of Pseudomonas aeruginosa . On similar lines, Bifidobacterium pseudocatenulatum SPM1309 was shown to inhibit MDR P. aeruginosa and A. baumannii ( 155 ). Lactobacillus casei strain exhibited strong activities against MDR Shigella strain ( 156 ).…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 88%
“…AL-Saadi reported that B. breve had antagonistic activity against methicillin-resistant S. aureus (MRSA) (21). Also, Lee reported that Bifidobacterium strain could have a potential application for alternative therapy in P. aeruginosa and Acinetobacter baumannii (22).…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases are the second largest cause of fatality in the world recording for more than 13 million deaths annually [4].…”
Section: Introductionmentioning
confidence: 99%
“…Overuse of antibiotics, use of unprescribed antibiotics and continuous use of topical antimicrobial agents has led to the condition where the pathogens become resistant to the used antibiotics [5]. Since the multidrug resistant strains have been increased, the choice of therapy often becomes very limited [4]. The reason for becoming multi-drug resistant in the wound infection is due to the misuse and overuse of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation